Digital innovations for renewable energy and conservation - Jain, Vishal; P., Jaheer Mukthar K.; Tsai, Sang Bing; Wu, Chia Huei (Advances in environmental engineering and green technologies (AEEGT) book series., 2025)
"With the growing urgency of climate change, digital innovations emerge as pivotal tools in advancing renewable energy and conservation efforts. From sophisticated data analytics that optimize energy efficiency to smart grids that enhance the reliability of renewable sources, technology is transforming how we produce, manage, and conserve energy. To harness the full potential of these renewable innovations, effective research into cutting-edge digital technologies and practices is necessary. Digital Innovations for Renewable Energy and Conservation delves into the intersection of digitalization and sustainable growth, exploring how advancements in technology can be leveraged to foster environmental sustainability and economic prosperity. It examines the evolving landscape of the global economy in the digital age, identifying opportunities and challenges for achieving sustainable development goals. This book covers topics such as climatology, smart cities, and digital technology, and is a useful resource for policymakers, business owners, computer engineers, environmentalists, conservationists, academicians, scientists, and researchers."--